Age of onset or age at assessment—that is the question: Estimating newly incident alcohol drinking and rapid transition to heavy drinking in the United States, 2002–2014. Issue 1 (15th October 2017) - Cheng, Hui G.; Lopez‐Quintero, Catalina; Anthony, James C.
Abstract: Age‐specific incidence estimates are important and useful facts in psychiatric epidemiology, but incidence estimation can be challenging. Methods artifacts are possible. In the United States, where the minimum legal drinking age is 21 years, recent cross‐sectional field research on 12‐ to 25‐year‐olds applied conventional "age‐at‐assessment" approaches (AAA) for incidence estimation based on 12‐month recall. Estimates disclosed unexpected nonlinear patterns in age‐specific incidence estimates for both drinking onset and for transitioning from first drink to heavy drinking. Here, our aim is to draw attention to an "age of onset" (AOO) alternative to AAA approaches and to verify whether the AOO approach also discloses nonlinearity. Yearly data are from U.S. nationally representative samples drawn and assessed for National Surveys on Drug Use and Health, 2002–2014, with standardized audio computer‐assisted self‐interview assessments for drinking outcomes. Both AAA and AOO approaches show nonlinearities, with an unexpected dip in drinking incidence rates after age 18 and before the age 21 minimum legal drinking age. The AOO and the AAA approaches disclosed similar age‐specific patterns. We discuss advantages of the AOO approach when nonlinear incidence patterns can be anticipated, but we conclude that the AAA approach has not created an artifactual nonlinear pattern.